The improvement of meter performance of EM sensing flowmeters using software modelling - Lim, Sungtaek (Cranfield University, 2008)
This thesis is focused on the improvement of the meter performance and power consumption of non-mechanical flowmeters such as the conventional electromagnetic flowmeter and the fluidic oscillator. Each flowmeter is studied using Finite Element Modelling for the magnetic field, the virtual current and the fluid dynamics in order to simulate flow signal. The meter design of the conventional electromagnetic flowmeter is modified to provide a better signal level by optimising the geometry of the flow channel and the magnetic field. The signal level increase can be used to reduce power consumption. This improvement provides a 1.96 times greater signal or 51% less power consumption for the conventional electromagnetic flowmeter. An alternative coil-less electromagnetic flowmeter is proposed to reduce the energy consumption. A laminated magnetostrictive material/PZT piezoelectric material is used to control the magnetic field from a permanent magnet. Modelling is carried out to optimise the meter and the magnetic field control device. The device can provide a further reduction of 54.7% of energy usage over the improved conventional electromagnetic flowmeter. The modelling of the fluidic oscillator is undertaken not only with the fluidic dynamics but also the flow signal by using the electromagnetic sensing technique. Using these approaches, recommendations for a better signal level are proposed.